New York and Homesickness in Ryhor Krušyna’s Poetry - Espinosa Ruiz, Angela (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
New York has been a meeting point for different cultures, languages and literary traditions for over a century, and poetry, as shown by examples as illustrious as Federico García Lorca’s A Poet in New York, is not an exception to this rule. Not only has New York served as a source of inspiration for local and foreign poets, but also as a physical hub for different, highly productive literary movements to develop, including two generations of the New York School, the Nuyorican Poets Café, the flourishing of the US slam poetry movement and, of course, a considerable part of the Belarusian American diaspora literary movement to which Ryhor Krušyna belongs, along with other prominent figures such as Natallia Arseńnieva or Masiej Siadnioŭ. The goal of our paper is to analyse the image of the Big Apple in the lyrical works of Belarusian poet Ryhor Krušyna, paying special attention to his expression of nostalgia and alienation, accentuated by the stark contrast between urban America and Krušyna’s native land. We will also analyse the main images of the poet’s symbolic system that contribute to his vision of New York and his poetic voice in this period of time, including the concept of distance, the feminine figures of the lover and the mother, and the elements of nature and urban spaces. In order to achieve this objective, we have chosen to examine his poetry cycle Lyric from the Big City, published in the Belarusian migratory poetry almanac Next to foreign shores, the first one of its kind, in 1955. We hope that our analysis of Krušyna’s New York poems will open a series of scientific and literary possibilities for research or all areas of literary theory in general and Slavic philology in particular, allowing comparative, theoretical and socio-historical analyses of Slavic poetry overseas to proliferate and develop.